Mobile AI Applications to Support QRIS Literacy and Financial Growth of Traditional Market SMEs - Dwianto, Agus; Qurrota A’yun, Annisa; Sabila, Isnayni (Inovasi Analisis Data, 2025)
Objective: The purpose of this research is to analyse how perceptions of mobile banking, the use of artificial intelligence (AI), literacy towards QRIS, and the level of trust in digital payment systems affect the adoption of QRIS by MSME players, with ease of use as a mediating variable.Methods: The survey 654 was analysed using a quantitative explanatory approach involving the further use of regression and mediation (Sobel) tests based on TAM and UTAUT model.Results: Results indicate that mobile banking familiarity, AI use, QRIS knowledge, and trust have significant relationships with digital payment adoption as influential factors directly, and indirectly through the mediator of perceived ease of use. Ease of use serves as a salient link between the behaviour and the technology. The use of AI is a new actually a new prime mover for establishing trust in digital interfaces. QRIS literacy is validated as a key facilitator and trust defuses accepted mistrust in low-tech settings.Novelty: This research’s contribution is the discussion of Artificial Intelligence (AI) which is utilized as behavioural facilitating in fintech adoption such as QRIS. Through the incorporation of AI usages into the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), this study enriches conventional models for intelligent financial ecosystems. This line of reasoning offers us new perspectives of how AI powered trust, personalization and automation affect user behaviour especially for MSMEs in semi-formal economic sectors.Practical Implications: The practical contribution of this research is to provide implications for policy maker, fintech developers, and MSME enablers by encouraging the need to improve the AI-based features, user trust, and easy to use of digital payment system such as QRIS. Enhancing digital literacy and incorporating user friendly mobile interface have potential to increase usage amongst MSMEs. In addition, promoting ethical use of AI can build user trust, helping to further broaden financial inclusion and sustainable digital transformation in Indonesia shaping semi formal economy.